Late Holocene high precipitation events recorded in lake sediments and catchment geomorphology, Lake Vuoksjávrátje, NW Sweden. (19th June 2015) - Berntsson, Annika; Jansson, Krister N.; Kylander, Malin E.; De Vleeschouwer, Francois; Bertrand, Sebastien
<x xml:space="preserve">Abstract</x> In this paper, we show the potential of combining multi‐proxy analysis of lake sediments with catchment geomorphology to better understand palaeoenvironmental changes. Previous studies have suggested that alpine lakes in N Sweden may be highly sensitive to variations in catchment erosion and precipitation, and that this sensitivity may influence ecologically based reconstructions of past temperature changes. We analysed lake sediments covering the last 5100 years from the alpine Lake Vuoksjávrátje in NW Sweden in order to identify different erosional regimes in the lake catchment, sediment sources and lake sedimentary processes, which ultimately affect the palaeoecological record. The measured proxies include elemental geochemistry from XRF core scanning, grain size, sediment accumulation rates, fraction of terrestrial organic carbon and geomorphological mapping, supported by previously published chironomid and total organic carbon data. From the integrated results we identified time intervals when increased intensity of precipitation altered sedimentation and lake catchment erosional processes. The most prominent event occurred c. 2900 cal. a BP and is interpreted to be the result of excessive precipitation, possibly related to the climatic shift towards cooler and wetter conditions referred to as the 2.8 ka event.